Worlds of Arthur : facts and fictions of the dark ages - Halsall, Guy (Oxford University Press, 2013)
King Arthur is probably the most famous and certainly the most legendary medieval king. From the early ninth century through the middle ages, to the Arthurian romances of Victorian times, the tales of this legendary figure have blossomed and multiplied. And in more recent times, there has been a continuous stream of books claiming to have discovered the 'facts' about, or to unlock the secret or truth behind, the 'once and future king'. Broadly speaking, there are two Arthurs. On the one hand is the traditional 'historical' Arthur, waging a doomed struggle to save Roman civilization against the.